Tourism studies: situated within multiple disciplines or a single independent discipline? (discursive article) - Liszewski, Stanisław (Turyzm/Tourism, 2011)
The article concerns the fundamentals of tourism studies and its methodology. After presenting the current situation, the author comments on the opinions of those whose aim it is to establish tourism studies as a fully independent discipline. This is followed by a presentation of the process of creating a ‘tourism studies’ which is not only multi-disciplinary, but above all an interdisciplinary basis for research. The article ends with a short reflection on the future of tourism studies and some conclusions. It is a discursive article.